Peran Masyarakat Retail Dalam Meningkatkan Ketahanan Ekonomi Nasional di Masa Pandemic - Sudarma, Ade (PT. Alahyan Publisher Sukabumi, 2023)
The webinar on the role of the retail community in increasing national economic resilience during the pandemic is one solution to the problems faced by the retail industry and the wider community, namely the lack of understanding regarding the strategies that must be taken to survive during the pandemic. The purpose of this activity is to increase understanding of the strategies implemented by the retail community in contributing to national resilience during the pandemic. The method of implementing this activity is a webinar for students, retail communities, high school students in Sukabumi City, and the general public. Partners in this webinar activity are the retail management study program, the Dikumindag of Sukabumi City, and the Cooperatives and SMEs Office of Sukabumi Regency. The evaluation was carried out by giving questionnaires to webinar participants before and after delivering the material, and the result was that the comprehension ability of the participants increased by 38.14%.